Beyond the single norm: how social perceptions connect in a norm network - Sparkman, Gregg; Weber, Elke U. (Frontiers in Social Psychology, 2023)
Our actions may be influenced not just by one norm, but by many interconnected norm perceptions. If so, how are such norm networks structured and how do they operate? Are norm prevalence perceptions in a population connected by similarity of content? Does influencing the perceived prevalence of one norm affect related norms, perhaps in a hierarchical fashion? And, for intervention purposes, are some norms more readily influenced than others? Over three studies (total N = 3,872), we examine dozens of norms in the context of environment and renewable energy and introduce a method to visualize norm networks, illustrating connections between many norms and personal attitudes. We find that norms are connected via similar perceived prevalence and similar content—two features that are highly interrelated—and that norm perceptions vary in terms of plasticity and content broadness. Further, norm updating spreads through networks: manipulating the perceived prevalence of one norm influences connected norms. The norm network approach represents a new way to conceptualize social influence and inform norm-based interventions, one that can go beyond a single norm and may help us better understand and harness the influence of social norms via a broader social reality.